Strategi Kepala madrasah dan Guru dalam Membina Akhlak Siswa di MTs - Mohammad Jawahir; Ismail Sukardi; Amilda Amilda (Studia Manageria, 2020)
This study aims to describe the strategy of the head of the madrasah in coaching students' morals and the strategy of the teachers in their guidance in MTs which includes planning, implementation andevaluation. This research is a descriptive study with a qualitative approach. The subjects of this study are the principal, teacher special class guidance, andstudents who are associated with this preaching class program. Data collection techniques using interviews, observation, and documentation. The data validity test usedsource triangulation techniques. Based on the learning management research the results of the study show that the headmaster in his strategy uses special classes, provides advice, provides habituation, exemplary,and holds student guardian meetings. Thus the monitoring of student development can be known and acted upon by the student guardian repat. As for the teacher using the way Habituation, exemplary, advice, stories of exemplary stories,andrewards (if they are good we also reply with wisdom, if we are wrong we law). Da'wah class is as a means for special students who experience problems that really need attention, parental agreement with the council of teachers, especially the head of medarasah and their cooperation is expected to realizethe vision and mission of the Madrasah Tsanawiyah.